Kepentingan Politik Jangka Panjang Mahkamah Konstitusi dan Fenomena Judicialization of Politics Pada Beberapa Putusannya: The Long-Term Political Interests of the Constitutional Court and the Phenomenon of the Judicialization of Politics in Some of Its Decisions - Zaky Badruzzaman (SIYASI: Jurnal Trias Politica, 2023)
This article aims to describe the phenomenon of judicialization of politics in Indonesia. This phenomenon became known at the beginning of the 21st century, which was marked by the resolution of matters relating to public policy, morality, education and political controversies through judicial institutions. The emergence of the judicialization of politics can be seen in the shift in the resolution of political conflicts which were previously resolved through political institutions, namely the MPR, to judicial-based resolution. To be able to see this phenomenon, this article will discuss the brief minutes of the formation of the Constitutional Court in Indonesia. From a socio-historical perspective, the establishment of the Constitutional Court is an institution that is not only intended to fulfill judicial interests, but also expands its presence into the political realm. Apart from that, this article will also explain the decision of the Constitutional Court regarding the institutional position of the Corruption Eradication Committee and the age limit for presidential and vice-presidential candidates to show that the phenomenon of judicialization of politics is clearly present in Indonesia through the Constitutional Court Decision.